Studies on microscopic technique and culture on Sabouraud’s dextrose agar medium for diagnosis of dermatophytes infection - Khan, Md Abul Abul Hossain; Khan, S M Atique Hasan; Sarker, Mahbub Rashid; Hussain, Rubiyat Farzana; Ahmed, Mejbah Uddin; Joarder, Yasmin; Hasan, Md Bulbul (KYAMC Journal, 2013)
Dermatophytoses (a fungal infection of the skin, hair and nail, usually caused by dermatophytes) constitutes an important public health problem because of its high prevalence and associated morbidity but not life-threatening. Three genera of dermatophytes are recognized based on the site and pattern of fungal invasion. Dermatophytes are the predominant pathogenic mould, but yeasts (especially Candida albicans) and non-dermatophytic moulds may also be implicated. For accurate diagnosis of dermatophytoses requires microscopic demonstration and isolation and identification by culture. This study evaluates the usefulness of microscopic technique and culture for the isolation and identification of dermatophytes from clinical samples. Thirty samples were included in this study for detection of fungal elements by both methods but sensitivity of microscopic demonstration and culture were 60.0% and 66.7% respectively. As the sensitivity of microscopic demonstration (60.0%) is almost equal to the isolation and identification rate (66.7%), requires further evaluation in large scale as its ready to use format makes the application and microscopy much easier and faster. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13658 KYAMC Journal Vol. 3, No.-1, June 2012 pp.235-238